2021
DOI: 10.48550/arxiv.2108.03241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The first nova eruption in a novalike variable: YZ Ret as seen in X-rays and gamma-rays

Kirill V. Sokolovsky,
Kwan-Lok Li,
Raimundo Lopes de Oliveira
et al.

Abstract: Peaking at 3.7 mag on 2020 July 11, YZ Ret was the second-brightest nova of the decade. The nova's moderate proximity (2.7 kpc, from Gaia) provided an opportunity to explore its multi-wavelength properties in great detail. Here we report on YZ Ret as part of a long-term project to identify the physical mechanisms responsible for highenergy emission in classical novae. We use simultaneous Fermi/LAT and NuSTAR observations complemented by XMM-Newton X-ray grating spectroscopy to probe the physical parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 184 publications
(268 reference statements)
0
9
0
Order By: Relevance
“…We found that the bipolar aspect of [Si ] only starts to appear in the models where the accretion disc is more luminous than the central component, and it is best observed for the models with Ṁ=5 × 10 −7 M ⊙ year −1 (Figure 13). However, an accretion disc with such a high mass transfer rate is hot and possibly thick at outer borders, resembling the discs obscuring the direct view of the white dwarf in some persistent and post-nova supersoft sources (Ness et al 2012(Ness et al , 2013Sokolovsky et al 2021). Probably, its precise SED and vertical structure, and thus its effect on the shell ionization can not be predicted with our simplified standard disc assumptions (Frank et al 2002).…”
Section: Resultsmentioning
confidence: 89%
“…We found that the bipolar aspect of [Si ] only starts to appear in the models where the accretion disc is more luminous than the central component, and it is best observed for the models with Ṁ=5 × 10 −7 M ⊙ year −1 (Figure 13). However, an accretion disc with such a high mass transfer rate is hot and possibly thick at outer borders, resembling the discs obscuring the direct view of the white dwarf in some persistent and post-nova supersoft sources (Ness et al 2012(Ness et al , 2013Sokolovsky et al 2021). Probably, its precise SED and vertical structure, and thus its effect on the shell ionization can not be predicted with our simplified standard disc assumptions (Frank et al 2002).…”
Section: Resultsmentioning
confidence: 89%
“…An observation with XMM-Newton, including use of the RGS grating and done 5 days earlier, explains the low flux: the system must be at high inclination, because no stellar continuum was detected. The spectrum was an emission line one (Sokolovsky et al 2021), probably due to photoionized ejecta and with no spectral signatures of shocked material in collisional ionization equilibrium. Although this conclusion cannot be reached by examining our NICER broad band spectrum, the bolometric luminosity derived is of order 1/1000 of that expected for a burning WD atmosphere, about the same as in the XMM-Newton observation, so clearly this does not support the possibility that the spectrum changed and the central WD SSS spectrum emerged during the 5 days intercurring between our NICER exposures and the data taken by Sokolovsky et al (2021).…”
Section: Nicer Observations Of Yz Retmentioning
confidence: 94%
“…The spectrum was an emission line one (Sokolovsky et al 2021), probably due to photoionized ejecta and with no spectral signatures of shocked material in collisional ionization equilibrium. Although this conclusion cannot be reached by examining our NICER broad band spectrum, the bolometric luminosity derived is of order 1/1000 of that expected for a burning WD atmosphere, about the same as in the XMM-Newton observation, so clearly this does not support the possibility that the spectrum changed and the central WD SSS spectrum emerged during the 5 days intercurring between our NICER exposures and the data taken by Sokolovsky et al (2021). In a different project collaboration, some of us observed the nova after another month with the Chandra LETG, and although the spectrum had considerably changed and softened in comparison with the observations reported by Sokolovsky et al (2021) and with our NICER broad band spectra, it was, once again, an emission line one, without a measurable stellar continuum (Drake et al 2020, andOrio et al 2022, in preparation).…”
Section: Nicer Observations Of Yz Retmentioning
confidence: 94%
See 1 more Smart Citation
“…A tool like HILIGT is especially important for sources typically studied in the X-rays, because they often show dramatic changes in luminosity (see, e.g., Remillard and McClintock 2006). Therefore, a further major application is research into outbursts and state changes of transient sources (see, e.g., Belloni et al 2011 or Hasinger and van der Klis 1989), as performed for instance in recent nova studies (Sokolovsky et al, 2021), or the ongoing eROSITA all-sky survey (e.g., Gokus et al 2020 or Malyali et al 2020). As it can be used to easily query the history of a source in the X-rays, HILIGT also bridges a connection to other multi-wavelength efforts such as ASSA-SN 2 , which often observe new transient phenomena.…”
Section: Introductionmentioning
confidence: 99%